Socjologia a religie. Współczynnik humanistyczny jako narzędzie wartościowania w pismach Ericha Fromma - Kaczmarek, Kamil (Uniwersytet im. Adama Mickiewicza, Wydział Teologiczny, 2003)
The first aim of this work is to describe the general theory of religion presented in the books of Erich Fromm. Particularly those elements of it that stand between the domains of philosophy, psychology and especially sociology of religion. It has been focused on his general theory of religion, useful to find out a solution to a problem of fundamental theology and other practical disciplines: how to value different religious phenomena from the over-confessional perspective. The scientific evaluation is required to overcome an ideological egalitarianism, i.e. an approach assuming that all religions are equal. The conception of Erich Fromm is treated here as a proposal of the instrument, which can be used for it and simultaneously that cannot be charged of the confessional bias. After Florian Znaniecki and Stanisław Kozyr-Kowalski we call this instrument a „humanistic coefficient". In the consecutive chapters separated elements of this theoretical instrument are described: the scientifically simplified Fromm's anthropology (chapter II), his concept of religion (chapter III) and his conception of the influence of various religions on human personality. The additional result of this work was that an unnoticed source of Fromm's thought is Herbert Spencer's sociology. Spencer's influence on Fromm can be seen in latter's key theory of social character. Frequent opposition in Fromm's writing: authoritarian vs. humanistic is an exact equivalent of Spencer's opposition: militant vs. industrial. It is worth noticing that term productive", which Fromm used interchangeably with „humanistic" is a precise translation of the old-English word industrial". Both thinkers agreed that Christianity in Europe is for the main part only a surface under which ancient pagan beliefs, e.g. Heroworship, nation-worship are hidden. Not always are Fromm's ideas better than Spencer's. In psychology and social psychology that is the case, however in sociology (e.g. sociology of religion) Fromm's ideas are considerable simplifications in comparison to Spencer's. Especially Spencer's dichotomic typology of industrial vs. militant, in the application to religion is a much more interesting theoretical tool than that of Fromm. The simplifications arose from practical rather than theoretical purposes of Fromm's works. Generally, Fromm's works on religion showed that the scientific valuation of religion is possible (even if his trial is not fully convincing) and that the egalitarian relativism is not the only solution. Naturally on a more sophisticated level any valuation by humanistic coefficient has to be relative, i.e. must take into account a different influence of different elements of different religions on different individuals in different conditions. This kind of approach, which lays stress on differences but doesn't stop at the statement of differentiation we call the relationism as distinguished from relativism which it oppose and overcomes.
Keywords: Erichh Fromm; Religie